The Development of Local Wisdom-Based Natural Science Module to Improve Science Literation of Students (Jurnal Pendidikan IPA Indonesia, 2017)
The vulnerability of communities in facing volcano disaster is one of the indicators of the low literacy of science. The low knowledge about volcanic material causes it needs to be packed in an attractive learning so that it can tap into the ability of students’ science literacy by using teaching materials that are closer to student learning environments. This research aims to develop the local wisdom-based natural science module on the theme of Mount Kelud eruption, which is both theoretical and empirical. The type of this research development is Research and Development (R D) by adapting the ASSURE instructional design. The results of this research are the validation results of theoretical feasibility of teaching materials based on the components of material feasibility of 87, 5% with very good category, components of presentation feasibility of 91, 7% with very good category, components of language feasibility of 88, 9% with very good category, components of local wisdom values of 87, 5% with very good category, and components of science literacy feasibility of 88, 9% with 88, 9% with very good category. The results of empirical feasibility are the test results of students’ science literacy with N-gain variation value of 0,2; 0,3; and 0,4 respectively with low, medium, and medium category. The results show that the developed local wisdom-based natural science module is suitable to improve the ability of students’ science literacy either theoretically or empirically.